Nonlinear Interaction Between Two Shear Waves in Elastic Material - Wesołowski, Z. (Engineering Transactions, 1991)
The investigations a.re based on the successive approximation method for the Mumaghan’s material. Two one-dimensional shear waves of arbitrary profiles propagate in the opposite directions. The correction terms are calculated analytically. One numerical integration is needed for the calculation of the interaction terms. The correction and the interaction terms represent the longitudinal and the transverse waves. For the wave profile of the form exp(–x2) the correction terms and interaction terms are calculated.